2023
DOI: 10.1136/emermed-2022-213003
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a prehospital HEART score in patients with possible myocardial infarction: a prospective evaluation

Abstract: IntroductionThe History, Electrocardiogram (ECG), Age, Risk Factors and Troponin (HEART) score is commonly used to risk stratify patients with possible myocardial infarction as low risk or high risk in the Emergency Department (ED). Whether the HEART score can be used by paramedics to guide care were high-sensitivity cardiac troponin testing available in a prehospital setting is uncertain.MethodsIn a prespecified secondary analysis of a prospective cohort study where paramedics enrolled patients with suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Modifying the ECG SNR 23 , ECG distribution shift 4,5 ), no guarantee exists these predictions will not be random or overconfident. Accordingly, as mentioned before, we encourage keeping the ECG interpreter in the loop 21 until predictive performance is at desired levels 3 . Whilst we showcase performance improvements, the work is still limited by various factors.…”
Section: /9mentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying the ECG SNR 23 , ECG distribution shift 4,5 ), no guarantee exists these predictions will not be random or overconfident. Accordingly, as mentioned before, we encourage keeping the ECG interpreter in the loop 21 until predictive performance is at desired levels 3 . Whilst we showcase performance improvements, the work is still limited by various factors.…”
Section: /9mentioning
confidence: 99%
“…Accordingly, the community has developed Machine Learning (ML) methods to improve the prediction of ACS with prehospital covariates 1 , 2 . Nevertheless, performance remains insufficient for safe rule-out or rule-in of ACS 3 . Current research in cardiovascular disease detection from ECG has observed a possible trade-off between performance and coverage (i.e.…”
Section: Introductionmentioning
confidence: 99%